A Wolf in Sheep’s Clothing? English Terminology in French Annual Reports of the European Central Bank from 1991 to 2008 - Camilla Ferard (JoSTrans: The Journal of Specialised Translation)
Nineteenth century ‘standard’ English was based on a rationalist and empiricist assumption of one sole ‘external’ reality which twentieth century ‘scientific’ linguistics transferred into the ‘internal’ mind. However, in the 1930s, Whorf’s studies suggested that different languages reflect different ways of seeing reality. In the 1980s, cognitive linguists also claimed that language works as a catalyst for creativity within different cultural environments.